A COMPREHENSIVE STUDY OF ASEEL CHICKEN REARING, FEEDING AND MARKETING: SOCIO-ECONOMIC IMPACTS ON FARMERS IN PUDUKKOTTAI DISTRICT - M. Dharani; A.P. Surendar (Indian Journal of Veterinary and Animal Sciences Research, 2026)
The study investigates the rearing practices and feeding systems of Aseel chicken in Pudukkottai District, Tamil Nadu, and a region where backyard poultry farming significantly contributes to rural livelihood. Data were collected from 60 farmers using structured questionnaire to assess their socio-economic profile, and management practices. Most farmers were categorized as small (51.67%) or marginal (36.67%) landholders, owning 2.5–5 acres of land, and considered poultry rearing as a secondary income source alongside agriculture, which was the primary occupation for 86.67% of respondents. Rearing systems predominantly followed the “all-in-all-out” method (55%), although housing and litter management practices often deviated from ideal standards. Only 15% of farmers provided recommended floor space of 1.5–2 sq. ft. per bird and litter thickness of 3–5 inches. Feeding practices relied heavily on scavenging (73.33%), with supplementary feeding using locally available ingredients such as broken rice, maize, and other grains. Single- type litter materials, like paddy husk, coir pith, or wooden shavings, were used by 83.33% of farmers. The study also found that the majority of farmers (66.67%) had medium experience in poultry rearing, averaging 15.48 years. Despite considerable traditional knowledge, there were notable gaps in adopting improved husbandry practices such as ideal housing, litter management, and supplementary feeding. These findings highlight the need for capacity-building initiatives to enhance farmers’ awareness and implementation of optimal rearing techniques, ultimately improving productivity and contribute to the sustainable livelihoods of rural communities.